Performance Evaluation of PFR and CSTR 1- Reactor Tank for Formaldehyde Petrochemical Production - Animia A, Wordu; Chidinma T, Elechi (International Journal of Chemical and Process Engineering Research, 2020)
CSTR 1-reactor tank and PFR plug flow reactor for the production of formaldehyde are two reactors subjected to performance studies. The research models were derived from the fundamental principles of conservation of mass and energy balance; and qualitative kinetic optimum model for the determination of yields for the dehydrogenation and partial oxidation of methanol in the two reactors at 600-6500C. The data obtained for model evaluation were statistically regressed to adopt it as engineering data which is adequate for applications in the evaluation process. The design models for the CSTR 1-reactor tank and PFR plug flow reactor reactors were appropriately solved. The results obtained on the two reactors parameters are given as follows: CSTR 1-reactor tank volume 2.85m3, Height 5.69m, Space-time 0.12hr, Space-velocity 0.67/hr, pressure drop and heat generated per unit volume 2.34*107J/m3. Similarly, PFR volume 1.26m3, Height 12.58m, Space-time 0.225hr, Space-velocity 0.182/hr, pressure drop 3.73*10-8 and heat generated per unit volume 1.17*108 J/m3, And, innovatively, results of optimal yields Yopt calculation for CSTR 1-reactor tank and Plug flow reactor PFR showed that the yields obtained for the two reactors are 69% and 87% and compare favorably with operational yields of the production process which stood at 78.5% and 80.1%. From the results PFR provide a better volume for the production of formaldehyde at 87% conversion of 1.26m3. Hence, the PFR has a better performance for the production of formaldehyde with 87% feed conversion.